Antibody-drug conjugates: the clinical development in gastric cancer - Zhu, Yingze; Zhou, Miao; Kong, Wenyue; Li, Congling (Frontiers in Oncology, 2023)
Gastric cancer (GC) is a prevalent malignant tumor of the digestive system worldwide, ranking among the top five in terms of incidence and mortality. However, the clinical efficacy of conventional treatments for gastric cancer remains limited, with a median overall survival of approximately eight months for advanced cases. In recent years, researchers have increasingly focused on antibody-drug conjugates (ADCs) as a promising approach. ADCs are potent chemical drugs that selectively target cancer cells by binding to specific cell surface receptors with antibodies. Notably, ADCs have demonstrated promising results in clinical studies and have made significant strides in the treatment of gastric cancer. Currently, several ADCs are under investigation in clinical trials for gastric cancer patients, targeting various receptors such as EGFR, HER-2, HER-3, CLDN18.2, Mucin 1, among others. This review offers a comprehensive exploration of ADC drug characteristics and provides an overview of the research progress in ADC-based therapies for gastric cancer.